2021
DOI: 10.4103/jisp.jisp_247_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of desensitizing dentifrices on dentinal hypersensitivity management: A scanning electron microscopic analysis

Abstract: Introduction: Dentin hypersensitivity (DH) adversely affects quality of life by impairing the ability to eat and drink certain foods, therefore, should be addressed promptly with a contingency plan that includes initial treatment with a noninvasive prophylactic home care approach, followed by in-office treatment if desired result is not achieved. Aim: The purpose of this study was to evaluate the effectiveness of four different pastes containing 5% NovaMin (Sensodyne Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Their electron microscope analysis showed more closed tubules in the arginine group than in the control. Midha et al [ 35 ] found positive effects for all anti-sensitive agents, with NovaMin, followed by arginine and potassium nitrate, most effective in closing dentine tubules. In contrast to Midha et al, Rajguru et al [ 36 ] reported arginine paste as more efficient in closing tubules but found NovaMin to resist acid challenges better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their electron microscope analysis showed more closed tubules in the arginine group than in the control. Midha et al [ 35 ] found positive effects for all anti-sensitive agents, with NovaMin, followed by arginine and potassium nitrate, most effective in closing dentine tubules. In contrast to Midha et al, Rajguru et al [ 36 ] reported arginine paste as more efficient in closing tubules but found NovaMin to resist acid challenges better.…”
Section: Discussionmentioning
confidence: 99%
“…In previous literature, physical blockage of tubules has proven more effective than reducing nerve excitability [ 35 , 56 , 62 ]. Studies show mixed results for desensitizers with potassium ions, with some expressing doubt [ 63 ] and others confirming their effectiveness [ 49 , 64 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dentin hypersensitivity adversely affects quality of life by impairing the ability to eat and drink certain foods, therefore, should be addressed promptly with a contingency plan that includes initial treatment with a noninvasive prophylactic home care approach, followed by in-office treatment if desired result is not achieved. For today, many studies have been conducted to assess the decrease in dentin permeability and the presence of nanoleakage in the resin-dentin complex when using universal adhesives (Midha et al, 2021). It was found that no adhesive system completely reduced dentin permeability.…”
Section: Introductionmentioning
confidence: 99%